PENERAPAN TPS DAN PP UNTUK MENINGKATKAN MOTIVASI MENULIS TEKS NARASI - Tati Mardewi (LPPM Universitas Bina Sarana Informatika, 2015)
The aim of this Classroom Action Research is to increase students’learning motivation and students’ narative text writingskill, by using Think Pair Share and Picture and Picture. This research is conducted at class VIII-8SMP Negeri 1 Ciomas of Bogor regency in Academic Year 2014-2015. The research is done by two cycles, each cycles consists of two actions. The deficiencies of the first cycle is reflected and improved in the second cycle. The goals’ criteria are achieved in the second cycle, it means that the classroom management by using Think Pair Share and Picture and Picture has been succeeded, so the reasearch is stopped. Based on the result of the research, students’ enthusiasm in the first cycle, 92,36% increases to 96,005% in the second cycle, students' learning motivation,78% in the first cycle increases to 83.8% in the second cycle. Students’ narrative text writing skills in the first cycle,72% increases to 81% in the second cycle. So it can be concluded that the result of the research showsthe classroom management by using Think Pair Share and Picture and Pictureis proved increasingenthusiasm, learning motivation and narrative text writing skill of the eighth grade of students’SMP Negeri 1 Ciomas of Bogor regency. Keywords: Think Pair Share (TPS), Picture and Picture (PP) , learning motivation, writing skill.